Предмет: Алгебра,
автор: vdasha691
Нужно срочно решение !
Приложения:
Ответы
Автор ответа:
1
27 - 2 = 3
х²+3х х х²-3х
27 - 2 - 3 = 0
х(х+3) х х(х-3)
х≠0 х≠-3 х≠3
Общий знаменатель: х(х+3)(х-3)
27(х-3)-2(х+3)(х-3)-3(х+3)=0
27х-81-2(х²-9)-3х-9=0
27х-81-2х²+18-3х-9=0
-2х²+24х-72=0
х²-12х+36=0
(х-6)²=0
х-6=0
х=6
Ответ: 6.
х²+3х х х²-3х
27 - 2 - 3 = 0
х(х+3) х х(х-3)
х≠0 х≠-3 х≠3
Общий знаменатель: х(х+3)(х-3)
27(х-3)-2(х+3)(х-3)-3(х+3)=0
27х-81-2(х²-9)-3х-9=0
27х-81-2х²+18-3х-9=0
-2х²+24х-72=0
х²-12х+36=0
(х-6)²=0
х-6=0
х=6
Ответ: 6.
Похожие вопросы
Предмет: Русский язык,
автор: anyta006
Предмет: Русский язык,
автор: tackvika
Предмет: Английский язык,
автор: artem229446
Предмет: География,
автор: nikitka10112
Предмет: Математика,
автор: karinakotova3462